A prescription audit in the ear, nose and throat outpatient department, in a tertiary care hospital: a descriptive cross-sectional study - Ninnekar, Savita Z.; Torvi, Janaki R.; Jasmine, Kadeeja P.; S., Abhyshek; E. H., Adarsh (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Prescription audit is a quality improvement process aimed at enhancing patient care and outcomes by reviewing prescriptions. It provides feedback to healthcare providers, (HCPs) to identify areas for improvement and ensure the quality of prescriptions. This study aims to analyse the prescription patterns and prescribing behaviour of doctors using world health organization (WHO) recommended core prescribing indicators and prescription audit guidelines from national health mission (NHM), India and implement action plan accordingly. Methods: A descriptive observational cross-sectional study was conducted for one month in the ear, nose and throat outpatient department (ENT OPD) of KMC-RI, Hubballi. A total of 96 prescriptions were analysed using WHO-recommended core indicators and additional indicators from a prescription audit template. An action plan was created to enhance prescription quality. Results: All the prescriptions contained complete demographic details of the patients, OPD registration name and date of consultation. Handwriting was legible in all 96 prescriptions with a score of 100%. Two lowest performing attributes were identified using prescription audit tool namely, allergy status and generic name with a score of 7% and 37.9% respectively. The study revealed that average number of drugs encountered was 1.9, the percentage of drugs prescribed by generic name was 37.9%, percentage of encounters with an injection prescribed was 2.08% and percentage of drugs prescribed from NLEM was 37.9%. Conclusions: The prescription audit revealed that most prescriptions adhered to WHO standards. However, improvements are needed in documenting allergy status and prescribing by generic name. An action plan with a defined timeline has been prepared to provide feedback, aiming to enhance prescription quality and ensure better healthcare outcomes.